Techniques Used by Teachers in Activating Studentsâ Schemata in Teaching Reading Comprehension at LBPP-LIA Padang - Azhari, Andry (STBA PRAYOGA PADANG, 2017)
AbstractThis research was aimed to: 1) identify the technique applied by LBPP-LIA teachers in Padang to activate the studentsâ schemata in teaching reading comprehension, 2) identify the application of the techniques found, 3) classify the use of technique for different level in LIA. The participants of this research were all teachers in LBPP-LIA Padang who taught in EA (English for Adult) program. This study is a descriptive research. The data was collected through observation, field notes and interview. The data was analyzed descriptively by putting the data in different arrays, making a matrix of categories and placing the data into categories and creating data displays. The findings of this study showed that there are 10 techniques used by LBPP-LIA Padang teachers in activating studentsâ schemata. They include previewing, pictorial context, questioning, semantic mapping, line drilling, the use of video and the combination of two until three of those techniques. It was also found that they also applied the technique in different ways. It means that one technique was conducted in different ways by different teachers. There were several consideration for them in choosing the technique.Key words: schemata , technique